Correlation of International Criminal Law and National Criminal Law in the context of the Russian-Ukrainian war - Navrotskyi, Viacheslav (Studia Iuridica Toruniensia, 2024)
The Russian-Ukrainian war has raised the liability issue for unleashing an aggressive war and participation in it. Without denying the significant role of international criminal law in fulfilling this task, it is important to use the means of national criminal justice as widely as possible. The article identifies both the factors which unite these two branches of law and those which determine the differences between them. The author describes the traditional areas of interaction between national and international criminal law, including: a) involvement of national legal systems in combating crimes for which the need to establish liability is recognized in international agreements; b) establishment of requirements (restrictions) at the international legal level for the use of criminal law repression in national criminal justice systems; c) direct use of the resources of the international community for criminalisation and penalization of certain acts and implementation of criminal law enforcement. The author argues that in the context of Russian aggression against Ukraine, traditional approaches to the relationship between international and national criminal law should be reconsidered, in particular in terms of the use of immunities, which are commonly used in international law: functional immunity of state representatives and combatant immunity.